Yield Stability of Sixteen Rice Genotypes in White Nile Sate, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of the present investigation was to analyze thepattern of Genotype x Environment (G x E) interaction for grain yield ofsixteen rice genotypes using Additive Main effects And MultiplicativeInteraction (AMMI) model. Genotypes were grown at two locations (Ed-duim and Kosti, White Nile State, Sudan) for two years. Main effects dueto environment (E), genotypes (G) and GxE interaction (GEI) weresignificant (p
Keywords: Rice; AMMI model; biplot; yield stability